Thalassaemia management: patients’ and family members’ perspectives - Muhammad, Siti Aeshah @ Naznin; Jantan, Abdul Wahab; Mat Zain, Nora; Abdul Rahman, Suzanah; Mohamed, Zulaiha; Abdul Rahim, Aidil Faszrul; Wan Su, Kamaruzaman; Wan Hassan, Wan Amal Hayati (2011)
Significant advances in the clinical management of thalassaemia has generally led to improved survival and quality of life.In Malaysia although significant progress has been made in the management of patients affected with thalassaemia, there are limited studies that look at the disease from the perspectives of the patients and family members.